Analysis and Evaluation of the Business Innovation Strategy: A Case Study of Apple Inc. - Siahaan, Marlina (Enigma Institute, 2023)
Studying business innovation at Apple Inc. involves examining the company's past accomplishments and analyzing the strategies, processes, and underlying beliefs that underpin this innovation. This research tries to uncover the various factors contributing to Apple's success in introducing groundbreaking commercial innovations that consistently push the limits of the technology sector. This study did a comprehensive descriptive analysis to investigate information regarding Apple's business innovation through in-depth case study analysis. Apple's business innovation extends beyond tangible items to encompass the ecosystem and total customer experience. Apple revolutionizes our interaction with technology through its integrated strategy, emphasis on design, and astute market analysis. However, there are ongoing difficulties in sustaining levels of innovation, being competitive, and retaining client loyalty in this constantly evolving era.